2002
DOI: 10.1007/s00268-001-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic wick: Does it reduce the incidence of wound infection following appendectomy?

Abstract: The role of prophylactic antibiotics is well established for contaminated wounds, but the use of antiseptic wound wicks is controversial. The aim of this work was to study the potential use of wound wicks to reduce the rate of infection following appendectomy. This prospective randomized controlled clinical trial was conducted at a university hospital in the department of surgery. The subjects were patients undergoing appendectomy for definite acute appendicitis. They were randomized by computer to primary sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…To a lesser degree (and maybe with the same rationale), the results were similar in the few studies reported over the last 40 years, which involved a subcutaneous wound drain [3]. Surprisingly, however, a wound pack (or wick) between a few loosely placed skin sutures bwas not associated with decreased wound infection rates following appendectomyQ in adults [4]. In our group 2 of 96 patients with a subcutaneous drain or pack only, we also did not see any improvement in the wound infection rate when compared with no treatment (group 1) (Table 1).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…To a lesser degree (and maybe with the same rationale), the results were similar in the few studies reported over the last 40 years, which involved a subcutaneous wound drain [3]. Surprisingly, however, a wound pack (or wick) between a few loosely placed skin sutures bwas not associated with decreased wound infection rates following appendectomyQ in adults [4]. In our group 2 of 96 patients with a subcutaneous drain or pack only, we also did not see any improvement in the wound infection rate when compared with no treatment (group 1) (Table 1).…”
Section: Discussionsupporting
confidence: 72%
“…Although most articles in the literature (both adult and pediatric) indicate that some form of antibiotic prophylaxis will diminish the incidence of wound infection after appendectomy for both acute and ruptured appendicitis [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], some authors still claim prophylaxis makes no difference [4,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto à prevenção de infecção com o uso de iodóforos (Grupo IV), a taxa de infecção obtida foi maior no grupo tratado com PVP-I comparativamente ao grupo controle (18) .…”
Section: Discussionunclassified
“…5,[9][10][11][12][14][15][16][17][18] Although some reports (both adult and pediatric, often combined) indicate that some form of antibiotic prophylaxis will diminish the incidence of both complications, 35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] others claim it makes no difference. 5,23,24,[27][28][29][30][31][32][33]36,[51][52][53][54] In our series, each ruptured appendix at operation had an obvious perforation confirmed by histopathological examination. The amount of peritoneal contamination varied between a small localized area in the right lower quadrant (15%) and gross contamination throughout the peritoneal cavity (85%).…”
Section: Discussionmentioning
confidence: 99%